Camel Milk Resistome in Kuwait: Genotypic and Phenotypic Characterization - Rita Rahmeh; Abrar Akbar; Batlah Almutairi; Mohamed Kishk; Naida Babic Jordamovic; Abdulaziz Al-Ateeqi; Anisha Shajan; Heba Al-Sherif; Alfonso Esposito; Sabah Al-Momin; Silvano Piazza (MDPI AG, 2024)
Antimicrobial resistance (AMR) is one of the major global health and economic threats. There is growing concern about the emergence of AMR in food and the possibility of transmission of microorganisms possessing antibiotic resistance genes (ARGs) to the human gut microbiome. Shotgun sequencing and in vitro antimicrobial susceptibility testing were used in this study to provide a detailed characterization of the antibiotic resistance profile of bacteria and their ARGs in dromedary camel milk. Eight pooled camel milk samples, representative of multiple camels distributed in the Kuwait desert, were collected from retail stores and analyzed. The genotypic analysis showed the presence of ARGs that mediate resistance to 18 classes of antibiotics in camel milk, with the highest resistance to fluoroquinolones (12.48%) and disinfecting agents and antiseptics (9%). Furthermore, the results pointed out the possible transmission of the ARGs to other bacteria through mobile genetic elements. The in vitro antimicrobial susceptibility testing indicated that 80% of the isolates were resistant to different classes of antibiotics, with the highest resistance observed against three antibiotic classes: penicillin, tetracyclines, and carbapenems. Multidrug-resistant pathogens including Klebsiella pneumoniae, Escherichia coli, and Enterobacter hormaechei were also revealed. These findings emphasize the human health risks related to the handling and consumption of raw camel milk and highlight the necessity of improving the hygienic practices of farms and retail stores to control the prevalence of ARGs and their transmission.